Peningkatan Kinerja Berbasis Manajemen Bakat, Servant Leadership Dan Komitmen Organisasi - Marno Nugroho; Bagas Dewantoro Pamungkas Putro (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to analyze the effect of talent management and servant leadership on HR performance through organizational commitment. The population in this study were all employees of PSDA-ESDM Semarang. The sampling technique using purposive random sampling is a sampling technique that uses certain criteria or considerations. Samples taken were 84 respondents, with a research instrument in the form of a questionnaire. Data analysis uses multiple linear regression. The results showed that talent management had a positive and significant effect on organizational commitment, Servant leadership had a positive and significant effect on organizational commitment. Talent management has a positive and significant effect on HR performance. Servant leadership has a positive and significant effect on HR performance. Organizational commitment has a positive and significant effect on HR performance. Organizational commitment is not able to mediate the influence of talent management and servant leadership on HR performance.